Triggering technological innovation through cross-border mergers and acquisitions: A micro-foundational perspective - Christofi, Michael; Vrontis, Demetris; Thrassou, Alkis; Shams, S. M. Riad (My University, 2019)
Over the past 30 plus years, the development of technological innovation through cross-border mergers and acquisitions (M&As) has captured an increasing amount of attention in business research and practice. The emerging literature on the topic addresses a significant phenomenon, however, it lacks theoretical underpinning and a cumulative empirical inquiry, from a micro-foundational perspective. Hence, a systematic and integrative research effort seems justified. Accordingly, we systematically review and analyze 30 articles published in 16 top-tier peer-reviewed journals from 1985 to 2018. We provide the first comprehensive systematic review of extant literature, include a critical analysis of these research efforts, identify several methodological, contextual and theoretical issues and problems that need to be addressed and offer avenues for future research. The paper concludes with an integrative framework that provides the basis for both theory and practice to further build on and be guided by.
Keywords: Cross-border mergers and acquisitions; Integrative framework; Micro-foundations; Systematic review; Technological innovation